HISTORICAL AND LEGAL ASPECTS OF FORMATION OF CIVIL SOCIETY - Khamidulla Djurabaevich Ruziev; Adelya Ildarovna Karimova (Web of Journals Publishing, 2024)
This article examines the historical development of civil society and is of greatest value. The problem of its formation and development is very important, especially in connection with the practical need to create a modern universal civil society.
Keywords: civil society, theory of great thinkers, era of enlightenment, human development, essence of civil society, phenomenon of civil society, philosophical treatises.